Coculture of Marine Streptomyces sp. With Bacillus sp. Produces a New Piperazic Acid-Bearing Cyclic Peptide - Shin, Daniel; Byun, Woong Sub; Moon, Kyuho; Kwon, Yun; Bae, Munhyung; Um, Soohyun; Lee, Sang Kook; Oh, Dong-Chan (Frontiers in Chemistry, 2018)
Microbial culture conditions in the laboratory, which conventionally involve the cultivation of one strain in one culture vessel, are vastly different from natural microbial environments. Even though perfectly mimicking natural microbial interactions is virtually impossible, the cocultivation of multiple microbial strains is a reasonable strategy to induce the production of secondary metabolites, which enables the discovery of new bioactive natural products. Our coculture of marine Streptomyces and Bacillus strains isolated together from an intertidal mudflat led to discover a new metabolite, dentigerumycin E (1). Dentigerumycin E was determined to be a new cyclic hexapeptide incorporating three piperazic acids, N-OH-Thr, N-OH-Gly, β-OH-Leu, and a pyran-bearing polyketide acyl chain mainly by analysis of its NMR and MS spectroscopic data. The putative PKS-NRPS biosynthetic gene cluster for dentigerumycin E was found in the Streptomyces strain, providing clear evidence that this cyclic peptide is produced by the Streptomyces strain. The absolute configuration of dentigerumycin E was established based on the advanced Marfey's method, ROESY NMR correlations, and analysis of the amino acid sequence of the ketoreductase domain in the biosynthetic gene cluster. In biological evaluation of dentigerumycin E (1) and its chemical derivatives [2-N,16-N-deoxydenteigerumycin E (2) and dentigerumycin methyl ester (3)], only dentigerumycin E exhibited antiproliferative and antimetastatic activities against human cancer cells, indicating that N-OH and carboxylic acid functional groups are essential for the biological activity.